Percursos de legitimação: caminhos da crítica em "O Alienista" - Silva, Ana Ferreira (2009)
This work aims at studying the critical fortune of O Alienista, related to the period from 1882 to 1982. Considering the discursive transformations of Machado de Assis criticism, we intend to do a bibliographical research and to reflect about the different interpretative methods which marked the literary criticism approaches in the period studied. Published in 1881 in the newspaper A Estação , this Machado de Assis work caused reactions from the critics, concerning singular changes introduced by him in the narrative form. Furthermore, the aforementioned date marked the maturity point and the domain of the author literary creation resources, which predicted a new phase in his work. However, the new narrative techniques presented to Brazilian literature imposed themselves as unusual codes of literary formalization and would make the critics reflect on the limits of expression and analysis. In this context, it was seen the first attempts of literary consciousness since Machado de Assis, who left us some noticeable lucidity essays, such as Notícia da atual literatura brasileira , published in 1873, and Eça de Queirós: o Primo Basílio , published in 1878. The first text would predict the style that would portray the production of the author s second phase, in which the fictional work characterizes itself as a rupture model with our cultural formation, guided by the European model, whose themes and techniques were related to the historical sense of nationality identification. In the second text, the author describes the production of the work of the Lusitan writer, to analyze, among other aspects, narrator, characters and verisimilitude. In both cases, Machado de Assis was the precursor of a new literature consciousness